Isolation Protein Hidrolyzat from Microalga Nitzschia sp. as A new Antimicrobial - Sakinah Nur Fadillah; Ahyar Ahmad; Hasnah Natsir; FAbdul Karim; Paulina Taba (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Microbial Fuel Cell (MFC) is a device that converts chemical energy to electrical energy through microbial metabolism. This research aimed to investigate the effect of electrolyte solution on electricity production and determine the content of bioethanol using Gas Chromatography-Mass Spectrometry (GC-MS) and refractometer through the fermentation process using Saccharomyces cerevisiae in molasses substrate. The method of this research uses a double chamber consisting of an anode and a cathode chambers connected through a proton exchange membrane (PEM). This research showed that the addition of KMnO4 0.2 M electrolyte solution generated a maximum current of 1.20 mA and a voltage of 480 mV with a power density of 2935 mW/cm2 resulted in a higher power density value than the addition of K3(Fe(CN)6 0.2 M electrolyte solution which only generated a maximum current of 1.65 mA and a voltage of 320 mV with a power density of 2690 mW/cm2. The results of the GC-MS analysis showed the presence of bioethanol and resulting bioethanol levels is 28.44%. The MFC system with molasses substrate has the potential to generate electricity and produce bioethanol at the same time